2005
DOI: 10.1242/jeb.01574
|View full text |Cite
|
Sign up to set email alerts
|

Arterial hemodynamics and mechanical properties after circulatory intervention in the chick embryo

Abstract: Altered blood pressure and flow impact cardiac function during morphogenesis. How the arterial system supports cardiac morphogenesis after circulatory disruptions is not well characterized. We manipulated arterial flow via left atrial ligation (LAL) or arterial load via right vitelline artery ligation (VAL) in HamburgerHamilton (HH) stage 21 chick embryos. Embryos were reincubated for 1·h (HH21), 14·h (HH24) or 30·h (HH27). At each stage we measured simultaneous dorsal aortic blood pressure and flow, and calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 41 publications
(48 reference statements)
3
60
0
Order By: Relevance
“…response to hypoxia noted in fetal and adult vertebrates and is consistent with published data in the early embryo (10,13,14,18,24,28,35,36). In contrast to the mid-and lategestation fetus, the early embryo does not compensate for impaired CV function by adjusting HR.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…response to hypoxia noted in fetal and adult vertebrates and is consistent with published data in the early embryo (10,13,14,18,24,28,35,36). In contrast to the mid-and lategestation fetus, the early embryo does not compensate for impaired CV function by adjusting HR.…”
supporting
confidence: 90%
“…In the current study, we tested the hypothesis that hypoxia alters both embryonic ventricular and vascular function and growth in the early embryo during the critical period of early morphogenesis when changes in ventricular and arterial function can produce permanent structural and functional alterations (12,13,24,(27)(28)(29). In response to chronic hypoxia from the onset of incubation, we noted decreased ventricular systolic function, increased arterial impedance, reduced arterial blood flow, and reduced embryo growth and survival.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Furthermore, the aortic arches are part of a system which includes the entire embryo and vitelline vasculature. Even a small amount of vascular reactance to pulsatile flow will become significant when summed over such a large circulation (Lucitti et al, 2005). The dynamic component of the forces impeding blood flow must also be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies using the chick embryo model have shown that epigenetic perturbations in blood flow can also lead to altered cardiovascular morphogenesis and congenital defects, implicating hemodynamics as a major environmental, epigenetic factor (deAlmeida et al 2007;Gessner 1966;Hogers et al 1999;Lucitti et al 2005;Reckova et al 2003;Sedmera et al 1999;Tobita et al 2005). This relationship has been validated for the global growth of the aortic arches by several studies, where changes in aortic arch perfusion by occlusion of a vitelline vein (Hogers et al 1999;Rychter and Lemez 1965), left atrial ligation (Hu et al 2009), manipulation of the outflow tract (Gessner 1966), or ligation of individual aortic arches (Rychter 1962) generated abnormal arch growth and defects in arch derivatives.…”
Section: Introductionmentioning
confidence: 99%